PERANCANGAN APLIKASI ANAGLYPH IMAGE DENGAN MENGGUNAKAN METODE CHROMATIC ANAGLYPHIC PADA CITRA BERDASARKAN BESARNYA JARAK PERGESERAN WARNA - Anggela, Dessy (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Over time, the film industry and itstechnology is increasing.It encourages humancuriosity to develop ways of doing their work so thatprocessing can produce more interestingentertainment. As one way to do is to do imageprocessing. One of Image processing method isanaglyph movie that is movie form that looks moreraised so that it looks like in 3D. However, becauseeach people has a different point of view, sometimesthe eyes have to work hard to get a clear picture sothat sometimes they had a headache and dizziness.to reduce this negative cause then designed anAnaglyph converter application to measure theaverage people's eyes ability to capture anaglypheffect with good. this application will reconstructthe 3D video from 2D video using Chromaticanaglyphic method. This is the simplest method formaking the 3D image. this application works byoutlining a video into frames. Then those frame willbe processing by the application. Result from thisprocessing is a complete anaglyph video with theshift distance can be re-adjusted by the user. Thetest results showed that the average human eye cancapture anaglyph effect with well at a distance shift46,76 pixel with 12 inc screen view and 1 M length.45,96 pixel with 12 inc screen view and 2 M length.46,32 pixel with 14 inc screen view and 1 M lengthand 46,48 pixel with 14 inc screen view and 2 Mlength.